Ecology and adaptation of legumes crops: A review. Issue 1 (April 2020) - Al-Tawaha, A R M; Al-Tawaha, A; Sirajuddin, S N; McNeil, D; Othman, Y A; Al-Rawashdeh, I M; Amanullah,; Imran,; Qaisi, A M; Jahan, N; Shah, M A; Khalid, S; et al.
Abstract: In this review, we discuss the relationship between environmental crop management and adaptation to warming climates of legume plants and plant breeding, for drought tolerance. The benefits connected to the impact of the expansion of appropriate legumes-based agriculture for arid zones are analyzed. We need to two aims to develop programs of breeding and management guided to drought tolerance. The first one is enhancing productivity. The second one is to improve the drought tolerance by mechanisms of water conservation.